PERAN FKUB DAN PENDIRIAN RUMAH IBADAT DI KOTA PEKANBARU - Erman Erman (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2010)
Religious conflicts tends to occur due radical-extreme and fundamental to the doctrine os subjective religious afilation. While external factors caused by attitude bedonitas and opportunity with the name of religion as a commodity interest. This attitude has made a prolonged humanitarian catastrophe. Disharmonitas these factors need to be reviewed in the relevance of religious relations in Indonesia. This is based on a framework of thinking, that one of the step to reduce conflicts was to determine this sources of the conflict itself, including the issue of the establishment of the synagogue, which authorized for the people of Religious Harmony forum